The Short Life of a Local Protest Movement: The Annexation Crisis of 1849-50 in the Eastern Townships - Little, J. (Journal of the Canadian Historical Association / Revue de la Société historique du Canada)

(untitled) (The Canadian Historical Association/La Société historique du Canada, 1992)
AbstractThis paper examines the annexationist movement on the border region of the Eastern Townships, where the American-descended majority felt that union with the United States would end their economic isolation and stagnation as well as remove them from the growing threat of French-Canadian political domination. Leading proponents of this genuinely bi-partisan movement were careful not to appear disloyal to Britain, however, and they actively discouraged popular protest at the local level. Fearful of American-style democracy, the local élite also expressed revulsion towards American slavery and militaristic expansionism. Consequently, the movement died as quickly in the Eastern Townships as it did in Montreal after Britain expressed its official disapproval and trade with the United States began to increase.